Towards General-Purpose Resource Management in Shared Cloud - Mace, Jonathan; Bodík, Peter; Fonseca, Rodrigo; Musuvathi, Madanlal; Musuvathi, Madan (HotDep'14: Proceedings of the 10th USENIX conference on Hot Topics in System Dependability, 2014)
In distributed services shared by multiple tenants, managing resource allocation is an important pre-requisite to providing dependability and quality of service guarantees. Many systems deployed today experience contention, slowdown, and even system outages due to aggressive tenants and a lack of resource management. Improperly throttled background tasks, such as data replication, can overwhelm a system; conversely, high-priority background tasks, such as heartbeats, can be subject to resource starvation. In this paper, we outline ve design principles necessary for eective and ecient resource management policies that could provide guaranteed performance, fairness, or isolation.We present Retro, a resource instrumentation framework that is guided by these principles. Retro instruments all system resources and exposes detailed, real-time statistics of pertenant resource consumption, and could serve as a base for the implementation of such policies.